Clinical outcomes and prognostic factors of bronchiectasis rheumatoid overlap syndrome: A multi-institution cohort study - Lin, Horng-Chyuan; Huang, Hung-Yu; Lin, Chun-Yu; Fang, Yueh-Fu; Lin, Chiung-Hung; Huang, Yu-Tung; Chang, Chiung-Hsin; Wang, Chun-Hua; Huang, Jhen-Ling; Liao, Ting-Wei; Hsieh, Meng-Heng (Frontiers in Medicine, 2022)
The information regarding bronchiectasis with RA (BROS) is limited in Asia. The objective of this study was to investigate the clinical characteristics and outcomes of BROS in Taiwan. This multi-institute cohort study included patients with BROS from January 2006 to December 2017. The clinical, functional and microbiological data of these patients were retrieved from the Chang Gung Research Database. Respiratory failure and mortality were the primary outcomes. Severe exacerbation was defined as bronchiectasis- related hospitalizations or emergency department visits. A total of 343 patients with BROS were identified. 108 patients had severe exacerbation and exhibited signiﬁcantly more previous exacerbations, a lower FEV1 and higher BACI score (11.1 vs 7.5) than patients without severe exacerbation. The most prevalent species in sputum were Nontuberculous mycobacteria (NTM) (14.8 %), Pseudomonas aeruginosa (14.2 %), and fungus (5.9%). 68.8% of BROS patients used disease modifying antirheumatic drugs (DMARD), 7.9% used biological DMARD. NTM and tuberculosis infection rates were higher in bDMARD group compared with nbDMARD group and others. Overall, the 3-year respiratory failure rate and mortality rate were 14.6% and 25.7% respectively. Patients with RA diagnosed before bronchiectasis had a signiﬁcantly higher cumulative incidence of mortality in a 3-year follow-up than those with RA diagnosed after bronchiectasis. In Cox regression, age, higher RF value and systemic steroid use were independent risk factors for mortality in BROS. BROS patients with severe exacerbation had a high mortality rate in Taiwan. Increased risk of NTM and tuberculosis infection was observed in patients with bDMARD.